HOAKS DAN UJARAN KEBENCIAN PERSFEKTIP AL-QURAN - Tang S, Muhammad (AZKIYA, 2019)
Social Media applications such as Facebook, Twitter, Intragram, Whatshap and others present as a tool for communication between people. If it is misused by humans, then social media will have a very big impact, including being used to slander or spread lies or untrue news, commonly called Hoax News. Starting with untrue news, anxiety arises in the community of distrust between one individual and another, or one group with another group so that blasphemous blasphemies arise between one another, who feel right this is also known as Hate speech or hate speech. The view of the Koran about this is that the Islamic Ummah must get accustomed to telling the truth and truth when interacting, using conscience addressing hoax and hate speech and the most important thing is to get accustomed to clarifying when there comes a news / news from the wicked who have not yet we know (foreign). Thus the Ummah will be peaceful, peaceful and avoid slander, unpleasant actions / remarks published by irresponsible people.